Tolerance Education in Local Cultural Wisdom Values (The Study At Ki Ageng Tarub Cultural Kirab, Tarub Village, Tawangharjo, Grobogan) - Ahmad Fauzi (Vol. 1 No. 1 (2022): Proceeding of International Conference Cultures & Languages 2022, 2022)
Indonesia is a pluralistic country, with the motto "Bhineka Tunggal Ika". With these different conditions, it is necessary to build a sense of tolerance among elements of society. Moreover, the issue of ethnicity, race, religion and culture often triggers conflicts in society. One of the ways to unite the community is the existence of local wisdom. This study intends to reveal how the education of tolerance in the values ​​of local cultural wisdom contained in the Ki Ageng Tarub Kirab, so that it can accommodate the relationship of tolerance between communities This research is a qualitative-explorative, case study with an ethnographic approach. Data collection techniques using interviews, observation and documentation. And data analysis uses interactive analysis which includes data reduction, data presentation and drawing conclusions. The result of this study is that the sense of tolerance contained in the local wisdom of Ki Ageng Tarub can develop well in the midst of society. Tolerance education within the framework of structurally functional local wisdom can unite different elements of society, creating social integration and highly respected social solidarity. The values ​​of tolerance education in local wisdom that are instilled include the value of solidarity, the value of harmony, the value of unity and mutual respect between elements of society.